A monopolização territorial e a (re) construção do território camponês em projetos de assentamento de reforma agrária - Borelli Filho, Dorival [UNESP] (2014)
This study aims to conduct a qualitative analysis of the Sustainable Development Projects (in Portuguese Projetos de Desenvolvimento Sustentável, PDSs) implemented by the INCRA/SP, in the region of Ribeirão Preto (SP), having territory as foundation of resilience and consolidation of its political project, in a comparative analysis with the processes of territorial monopolisation engendered by the agro-industrial capital on conventional settlement projects (in Port. Projetos de Assentamento, PAs), a recurrent phenomenon in the Araraquara region. In this context, this analysis seeks to demonstrate the transforming nature of peasants' social movements when territorializing, introducing logic and socio-spatial practices capable of producing differentiated territories and territorialities, social transformations and disruptions in the clash with the logic and socio-spatial practices engendered by agro-industrial capital. For that purpose, in addition to a literature review of theoretical character and secondary data collection, semi-structured interviews with settlers social groups where conducted in this study, providing voice to the subjects of agrarian reform. Based on the data collected in the field, this study considers that the socio-spatial practices express the territorial dimension of the subjects and, therefore, the conditions for affirmation and denial of its historical trajectory as a (peasant) class, producing distinct/opposing spatialities. The conventional settlement projects (PAs) with strong process of territorial monopolization by capital denote practices which transfigure the peasant ethos while establishing social and productive relations through the logic of the commodity, of the income from the land and of transformation or prominence of exchange value over the use value of land. The environmentally differentiated settlement projects (PDSs) with socio-spatial trajectories or practices lead to the core of the forms...